Feasibility of Emergency Department–initiated, Mobile Health Blood Pressure Intervention: An Exploratory, Randomized Clinical Trial. (19th February 2019) - Meurer, William J.; Dome, Mackenzie; Brown, Devin; Delemos, Destinee; Oska, Sandra; Gorom, Victoria; Skolarus, Lesli
Abstract: Objectives: We aimed to assess the feasibility of a text messaging intervention by determining the proportion of emergency department (ED) patients who responded to prompted home blood pressure (BP) self‐monitoring and had persistent hypertension. We also explored the effect of the intervention on systolic blood pressure (sBP) over time. Methods: We conducted a randomized, controlled trial of ED patients with expected discharge to home with elevated BP. Participants were identified by automated alerts from the electronic health record. Those who consented received a BP cuff to take home and enrolled in the 3‐week screening phase. Text responders with persistent hypertension were randomized to control or weekly prompted BP self‐monitoring and healthy behavior text messages. Results: Among the 104 patients enrolled in the ED, 73 reported at least one home BP over the 3‐week run‐in (screening) period. A total of 55 of 73 reported a home BP of ≥140/90 and were randomized to SMS intervention ( n  = 28) or control ( n  = 27). The intervention group had significant sBP reduction over time with a mean drop of 9.1 mm Hg (95% confidence interval = 1.1 to 17.6). Conclusions: The identification of ED patients with persistent hypertension using home BP self‐monitoring and text messaging was feasible. The intervention was associated with a decrease in sBP likely to be clinically meaningful. Future studies are needed to further refine this approach and determine its efficacy.